5-(4-Methylphenyl)-1,3,4-thiadiazol-2-amine - Guan, Jian-Ning (International Union of Crystallography, 2009)
The title compound, C(9)H(9)N(3)S, was synthesized by the reaction of 4-methyl-benzoic acid and thiosemicarbazide. The thiadiazol ring adopts a planar conformation and makes a dihedral angle of 31.19 (18)° with the phenyl ring. In the crystal, molecules are linked by N—H⋯N hydrogen bonds.